2017
DOI: 10.1039/c6ra28503a
|View full text |Cite
|
Sign up to set email alerts
|

A novel h-BN–RGO hybrids for epoxy resin composites achieving enhanced high thermal conductivity and energy density

Abstract: In recent decades, significant attention has been focused on developing composite materials with high thermal conductivity utilizing h-BN, which has outstanding thermal conductivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 54 publications
4
31
0
Order By: Relevance
“…The introduction of GS with continuous 3D network promoted the dispersion of BN and remove agglomeration. The BN/epoxy composites usually existed the agglomeration of BN which blocked the effective heat transport along the composites and weak interaction between BN and polymer matrix . The agglomeration generated serious phonon scattering among the contacts with the BN particles, which was similar to the reports in the case of SiO 2 .…”
Section: Resultssupporting
confidence: 68%
“…The introduction of GS with continuous 3D network promoted the dispersion of BN and remove agglomeration. The BN/epoxy composites usually existed the agglomeration of BN which blocked the effective heat transport along the composites and weak interaction between BN and polymer matrix . The agglomeration generated serious phonon scattering among the contacts with the BN particles, which was similar to the reports in the case of SiO 2 .…”
Section: Resultssupporting
confidence: 68%
“…An exceptional high thermal conductivity has been reported due to the synergic effect of hybrid systems . Hybrids of graphene or graphite with MWCNT showed an important synergy and improved κ more than 120 % respect to the neat epoxy resin and 90 % respect to the composites containing individual MWCNT or graphene.…”
Section: Properties Of Epoxy Nanocompositesmentioning
confidence: 99%
“…The authors reported a thermal conductivity of 5.06 W/mK for the epoxy composites with 65 vol.% hybrids, which is 27 times higher than the neat epoxy resin. Huang et al . also fabricated an organic‐inorganic hybrid made of hexagonal boron nitride, h‐BN and reduced GO.…”
Section: Properties Of Epoxy Nanocompositesmentioning
confidence: 99%
“…Figure , the graphite gave an intensive peak at 26.1°and graphene at 25° which effected its (002) crystal plane that could lead to increase in d‐spacing from 3.41 to 3.56 Å, further the formation of a monolayer of graphene nanosheets have occurred. In Figure , G/BN‐20% composite contain an intensive peak that occurred at 26.7° which corresponds to (002) lattice plane of h‐BNNNS and the sharp peak was observed at 21.2° which was similar to that of graphene peak . It was concluded that the formation of the G/BN composite.…”
Section: Resultsmentioning
confidence: 86%